Literacy and power - Janks, Hilary (Language, culture, and teaching., 2010)
In this book--a landmark text that is both engaging and accessible--Hilary Janks addresses the following questions and many more:. Is literacy a skill or a social practice?. In what ways is literacy embodied?. Do texts have designs on us and what can we do about it?. How does language construct reality?. What is "linguistic capital" and who has it?. Who gets access to new literacies and who is excluded?. How is literacy implicated in relations of power and questions of identity in our daily lives?. Janks shows how competing orientations to critical literacy education--domination (power)